A Case of Refractory Oral Lichen Planus Successfully Controlled by Systemic Cancer-Chemotherapy for Recurrent Thymoma - Nagashima, Fumio; Maesono, Tomohiro; Fujiwara, Masachika; Kamma, Hiroshi; Kawai, Kirio; Shimoyamada, Hiroaki; Ikeda, Tetsuya; Hironaka, Hidekazu (JOURNAL OF THE KYORIN MEDICAL SOCIETY, 2023)
Thymoma is a rare disease with an incidence of about 0.5 per 100,000 people, and 0.3-6.3% of thymoma are accompanied by painful and intractable oral lichen planus, OLP. Symptomatic relief of OLP by thymectomy is reported to be not effective, and treatment by systemic chemotherapy for recurrent thymoma is rarely reported. We report the case of a woman in her 40s with no particular medical history. She was incidentally pointed out for a mediastinal tumor by a routine medical check-up, and diagnosed as thymoma pStage IVa. Thymoma was resected, but 6 months after resection thymoma recurrenced. Although local radiotherapy was performed four times in total, thymoma progressed, and resulted in radiotherapy-refractory Thymoma, accompanied by OLP. Systemic chemotherapy as PAC (cisplatin, adriamycin, cyclophosphamide) regimen for unresectable thymoma controlled not only thymoma, but also refractory OLP. After systemic chemotherapy for unresectable thymoma, there has been no recurrence of OLP. Survival period is approximately 8 years from surgery of thymoma.